EFEKTIVITAS TERAPI CERMIN TERHADAP PERBAIKAN MOTORIK LENGAN PASIEN STROKE ISKEMIK AKUT - Machyono,* Andi Kurnia Bintang,* Jumraini Tammasse,* Cahyono Kaelan,* Abdul Muis,* Idham Jaya Ganda* (Neurona Majalah Kedokteran Neuro Sains, 2018)
INTRODUCTION DISABILITY AFTER STROKE OFTEN HAPPENS AND BURDEN PATIENTS TO PERFORM THEIR DAILY ACTIVITY MIRROR THERAPY IS AN INTERVENTION FOCUSED ON HAND AND LEG MOVEMENT OF THE AFFECTED SIDE BASED OF MIRROR NEURON PRINCIPAL THIS NEW TECHNIQUE USING MIRROR IS SIMPLE AFFORDABLE AND EFFECTIVE